Pengaruh Frekuensi Notifikasi Media Sosial terhadap Konsentrasi Belajar pada Mahasiswa di Daerah Istimewa Yogyakarta - Ica Ananda Putri; Farah Anindya Wahyu; Asad Rifqi Habiburrahman (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid advancement of digital communication technology has made social media an important part of students' academic lives. However, the high frequency of social media notifications has the potential to distract attention and reduce concentration on learning. This study aims to identify the correlation between the number of social media notifications and students' focus on learning in the Special Region of Yogyakarta. The researcher applied a quantitative approach with an explanatory type. Data collection utilized an online questionnaire from 109 active students selected through the use of purposive sampling techniques. The research instrument consisted of 24 questions that had been tested for reliability and validity. Data processing utilized simple linear regression analysis operated through SPSS software version 30. Based on the research findings, the high intensity of social media notifications was proven to have a significant impact on students' concentration levels, as indicated by a significance value of <0.001. In addition, the coefficient of determination (R²) of 0.736 indicates that 73.6% of the changes in students' concentration can be explained by the variable of social media notification frequency, while the remaining 26.4% is influenced by other variables outside the scope of this study. These findings confirm that the more often students receive social media notifications, the greater the risk of decreased study concentration, making the management of notifications important in supporting learning effectiveness in the digital era.